Exogenous leukemia inhibitory factor (LIF) attenuates retinal vascularization reducing cell proliferation not apoptosis - McColm, Janet R. (2006)
To study the effect of leukemia inhibitory factor (LIF) on rat retinal vascular development, Sprague–Dawley rats at postnatal age 3 days (p3) were given intraperitoneal (IP) LIF and analysis performed at p6 (p3/6). p7 rats were given intravitreous (IV) LIF and analysis performed at p9 (p7/9). Control animals were PBS injected. At the time of analysis retinal flatmounts were prepared and stained with Griffonia lectin and activated caspase-3. The retinal peripheral avascular area was measured and number of apoptotic cells counted. In vitro, human retinal microvascular endothelial cells (RMVECs) were cultured in media containing LIF, with and without neutralizing antibody to LIF. Cells were stained with activated caspase-3 and apoptotic cells counted. Proliferation was measured by counting cell numbers, and cell cycle stage was determined using propidium iodide staining and FACS analysis. LIF injected either IP or IV had no effect on body weight or total retina area, but significantly increased the peripheral retinal avascular area. In both IP and IV injected groups there was no difference in the number of apoptotic cells between PBS-or LIF-injected groups; although in the p7/9 retinas, both injected groups had significantly more apoptotic cells than the non-injected group. In vitro, there was no effect of LIF on RMVEC apoptosis; however, cell counts were significantly lower in the LIF-treated group. Antibody to LIF restored the cell counts to untreated levels. LIF reduced the number of cells in S phase. LIF attenuates retinal vascular development in vivo through growth arrest, and not apoptosis, of endothelial cells.